Islamic literacy as a preventive effort against domestic violence: Analysis of the meaning of wadhribuhunna in An-Nisa' verse 34 - Thamrin, Thamrin; Ismail, Hidayatullah (Privietlab, 2026)
Cases of Domestic Violence (KDRT) against women have increased significantly, both physically and psychologically. In this context, Surah An-Nisa' verse 34 provides gradual guidelines for dealing with nusyuz, including moral warnings that are often translated literally as